1993
DOI: 10.1136/jech.47.6.436
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of seafood intake in pregnancy as a determinant of birth weight: evidence for a dose dependent relationship.

Abstract: Study objective-The aim was to explore whether maternal consumption of seafood is a determinant of birth weight in a dose dependent manner. Design-A population based survey of lifestyle factors in pregnancy was linked with information from antenatal and obstetric records. Setting and participants-Seventy five per cent of all 1362 women who delivered in the Faroe Islands during the study period 1986-87 who gave a structured post partum interview on lifestyle factors. Main results-Altogether, 2, 6, 16, 33, 26, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 7 publications
6
86
2
Order By: Relevance
“…The Excess condition in our rats did not have significant effects on birth weights, gestational length or other birthing variables; whereas several human studies showed such effects in infants born to women who consumed the highest amounts of seafood [17][18]30,[32][33]38,45]. Thus, our Excess condition in the rat was less toxic than the high dose condition in humans.…”
Section: Comments On Dosingcontrasting
confidence: 57%
“…The Excess condition in our rats did not have significant effects on birth weights, gestational length or other birthing variables; whereas several human studies showed such effects in infants born to women who consumed the highest amounts of seafood [17][18]30,[32][33]38,45]. Thus, our Excess condition in the rat was less toxic than the high dose condition in humans.…”
Section: Comments On Dosingcontrasting
confidence: 57%
“…The prevalence of small for gestational age (SGA) in the Norwegian Mother and Child Cohort Study (MoBa) is 6?6 % and the prevalence of low birth weight (,2500 g) is about 4?6 % in the MoBa cohort and 0?7 % in children born at term (.37 weeks of gestation) (19,20) . Positive associations between seafood consumption during pregnancy, and in particular lean seafood, and birth weight and SGA have been found in several studies, including the present cohort, while a few studies report inverse associations (21,22) . These inverse associations are often connected to the presence of environmental toxicants like polychlorinated biphenyls (PCB) and Hg (23,24) .…”
mentioning
confidence: 85%
“…This finding indicates that the difference determined for heavy smokers in the east-and westcoast cohorts originated not only from a long median time to pregnancy for heavy-smoking women in the eastcoast cohort, but also from a relatively short median time to pregnancy for heavy-smoking women from the westcoast cohort. Several studies have found a positive correlation between the consumption of noncontaminated fish during pregnancy on one hand and birthweight and duration of pregnancy on the other (27,28), but other reproductive outcomes have not been investigated. Thus whether a high intake of noncontaminated fatty fish is a positive factor for fertility can only be a matter of speculation.…”
Section: Discussionmentioning
confidence: 99%